School Management in the Midst of Educational Technology Advancement (European Journal of Teaching and Education, 2020)
This qualitative study has been intended to explore school management practices in the midst of educational technology advancement. Case study research design has been employed to have an in-depth look at practices of a selected school on adopting technology-driven school management in a way that addresses the type of technologies introduced and how they have contributed to school management. Accordingly, the school has so far introduced different educational technologies within a short period of time. Though positive roles of the introduced educational technologies on improving the existing school management have been recognized by regulatory bodies, further content and context-based studies and assessments need to be initiated in a way that enables expansion of the school’s best practices to other private and public schools in the metropolitan.